2009
DOI: 10.1002/aic.12003
|View full text |Cite
|
Sign up to set email alerts
|

Bubble size distribution modeling in stirred gas–liquid reactors with QMOM augmented by a new correction algorithm

Abstract: Local gas hold-up and bubbles size distributions have been modeled and validated against experimental data in a stirred gas-liquid reactor, considering two different spargers. An Eulerian multifluid approach coupled with a population balance model (PBM) has been employed to describe the evolution of the bubble size distribution due to break-up and coalescence. The PBM has been solved by resorting to the quadrature method of moments, implemented through user defined functions in the commercial computational flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 52 publications
0
57
0
2
Order By: Relevance
“…Values of k max from the drop size up to 10 times, the drop size were used for the modelling the drop breakup. 7,45,51 An exception is a recent work of Becker et al 27 who suggested that k max should be in the order of 100 times of the drop. In our work, k max was set to be equal to the drop diameter while it was assumed that larger eddies will transport the drop.…”
Section: Population Balance Modellingmentioning
confidence: 91%
See 2 more Smart Citations
“…Values of k max from the drop size up to 10 times, the drop size were used for the modelling the drop breakup. 7,45,51 An exception is a recent work of Becker et al 27 who suggested that k max should be in the order of 100 times of the drop. In our work, k max was set to be equal to the drop diameter while it was assumed that larger eddies will transport the drop.…”
Section: Population Balance Modellingmentioning
confidence: 91%
“…Laakkonen et al 8 adjusted the value of C 4 against experimental data, while others 45,53,54 assigned the value of C 4 according to the mechanism of breakup. In this work, we used ternary breakage mechanism into comparable size fragments, however, the effect of C 4 on the final drop size was tested as well.…”
Section: Population Balance Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Petitti et al (2010) pointed out that the terminal velocity of bubbles is further decreased at high gas hold-ups (above 5%). This condition is induced by an increased collision frequency between bubbles, which interferes with the rising motion.…”
Section: Gas Hold-upmentioning
confidence: 99%
“…Accordingly, when the abscissas or weights goes to null, the values will approach to lower limits of values. Avoiding this problem, a reconstruction of matrix A in a linear system by calculating of moments then applying a correction algorithm [67] may be used but it is not applied in current simulations. The measurement of particle size is done by collecting the particles in the pressurized tank.…”
Section: Summary and Implementation Of The Mean Velocity Effect In Tumentioning
confidence: 99%